1984
DOI: 10.1159/000287786
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Alopecia areata

Abstract: 48 patients with alopecia areata, 30 with common baldness, 30 with fungal infections underwent the Paykel’s Interview for recent life events. In the 6 months preceding onset, alopecic patients reported 123 events (x = 2.56), patients with common baldness 22 events (x = 0.73), patients with fungal infections 15 (x = 0.50) (p < 0.001). Events with negative impact, exits from social fields, uncontrolled events and socially desirable and undesirable events were significantly more frequent in alopecic patients than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 8 publications
1
30
0
4
Order By: Relevance
“…Mac Alpine [26], however, found no evidence to suggest that emotional factors play a significant role in the disease. Nevertheless, it does remain possible, as shown in a 1984 study [27], that severe emotional stress could be a precipitating factor in certain cases. This does not totally contradict an immunological view of its pathogenesis, since alterations of immune function can occur under conditions of severe psychological stress [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Mac Alpine [26], however, found no evidence to suggest that emotional factors play a significant role in the disease. Nevertheless, it does remain possible, as shown in a 1984 study [27], that severe emotional stress could be a precipitating factor in certain cases. This does not totally contradict an immunological view of its pathogenesis, since alterations of immune function can occur under conditions of severe psychological stress [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, controlled retrospective investigations began to appear in the literature, contributing to a better understanding of the role played by stressful life events in alopecia areata [42, 68, 69, 70, 71, 72, 73, 74, 75]. The results of these studies, as well as the characteristics of subjects and procedures, are summarized in table 2.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…The incidence of its differ ent types seems to vary from country to coun try [2,3], A great variability of etiological fac tors has been associated with this disorder, including immunologic changes, endocrine factors, infections, physical or psychological trauma [1,3,4], Stressful life events have been reported as precipitating factors in alopecic patients [5][6][7], Many authors found a significant association between anxiety and affective disorders and onset of AA [5,[7][8][9], However, other authors did not confirm such an association [10,11]. The course of AA is often unpredictable: general and topic treat ments are often uneffective.…”
Section: Introductionmentioning
confidence: 99%